Positive Response of Hyoscyamus pusillus Callus Cultures to Exogenous Melatonin on Biochemical Traits and Secondary Metabolites under Drought Conditions - Shamil I. Neamah; Nisreen A. Jdayea (International Journal of Agronomy)
There is increased attention from specialists toward producing natural compounds from plant tissues through the combined use of elicitors. The present study investigated the effects of melatonin treatment in normal and drought stress conditions for sustainable production of biomass and secondary antioxidant metabolites in a Hyoscyamus pusillus four-month-old callus cultures. For this purpose, we used multiple concentrations of melatonin (0, 0.5, 1.0, 1.5, and 2.0 mg l−1) to assess its ability to improve growth, physiological, and biochemical properties of H. pusillus. There was two drought stress levels (0 and 30 g l−1) of polyethylene glycol (PEG). It was harvested in 28 days. The results showed a significant decrease with an increase in the concentration of PEG treatment in growth and physiological traits compared to the results of those samples when treated with melatonin. Results showed an increase in oxidative stress in tissue treated with PEG due to a significant increase in the content of hydrogen peroxide (H2O2) and malondialdehyde (MDA). The decreased oxidative stress was associated with an increased antioxidant enzyme activity superoxide dismutase (SOD), and catalase (CAT) in the samples was treated by melatonin, which resulted in increased membrane stability index (MSI) and enhanced growth traits under the PEG treatment compared to the control. By reducing the activity of phenylalanine ammonia-lyase (PAL) and peroxidase (POX), moisture tightening increased the production of phenolic compounds (PC) and flavonoid compounds (FC) in callus cultures, and high concentrations of melatonin were combined with them to improve their production. Therefore, it can be asserted that a moderate treatment with melatonin is more suitable under water stress conditions to produce secondary compounds from H. pusillus.